Bridging Languages: How EMI Teachers Use Language-related Teaching Strategies in their Classrooms - Meta Sekar Dewani; Debora Tri Ragawanti (ETERNAL (English Teaching Journal), 2026)
The rapid expansion of English-medium Instruction (EMI) in higher education worldwide presents opportunities and challenges, particularly in non-English-s contexts. While EMI aims to enhance global competitiveness, academic quality, and intercultural awareness, its implementation often faces language-related barriers affecting both students and instructors. This study investigated the language-related teaching strategies international EMI teachers employed to facilitate content delivery and enhance student comprehension. Specifically, it explored the instructional and regulative discourse strategies utilized in EMI classrooms. A case study approach was employed, focusing on two international EMI teachers at a private university in Indonesia. Data were collected through classroom observations, stimulated recall, and semi-structured interviews. Findings reveal that teachers used various instructional strategies, including demonstrations, visual aids, synonyms, and code-switching, to bridge linguistic gaps and support content comprehension. Regulative strategies such as building rapport and checking comprehension were also frequently utilized to create an inclusive learning environment. Teachers perceived these strategies as effective in mitigating language-related barriers and fostering engagement among students with varying English proficiency levels. This study underscores the importance of language awareness in EMI pedagogy and offers insights into effective teaching strategies for non-language faculty delivering content in English.